ANALISIS KEABSAHAN PEMEGANG SERTIPIKAT TANAH DENGAN ADANYA SENGKETA SERTIPIKAT GANDA (CONTOH KASUS: SERTIPIKAT GANDA DENGAN NOMOR PERKARA 321/PDT.G/2018/PN SMG) - Clara Regina Febriella (Jurnal Hukum Adigama, 2021)
Land is considered very important for human life, not only in life, even at death humans also need land. The important role of land makes people want to acquire and control the land. The desire to control this land eventually resulted in land disputes, one of which was the existence of a dual land certificate in a piece of land that was officially issued by the National Land Agency. As a result of dual certificates with the accumulation of rights in part or in full, resulting in a dispute for the parties concerned. On the community side, land issues, especially the issue of dual land certificates, have not been fully realized, and only realized after someone else also had a land certificate on the land they owned. Due to the community's ignorance of the dual land certificates, he could not take any preventive measures. The purpose of this paper is to try to provide information, reduce, and prevent the occurrence of double certificates of land. The government as the person responsible for the occurrence of double certificates must have courage and firmness in enforcing land law. In addition, the government should be able to provide information on a regular basis about certificates so that the public knows all the possibilities that cause double certificates to occur.